Investigation of the impact of hydrodynamic conditions on sediment resuspension in shallow lakes. Issue 1 (31st December 2022) - Luo, Wenguang; Lu, Jing; Zhu, Senlin; Yue, Yao; Xiao, Lingjun
ABSTRACT: In this study, we sampled the original sediment columns from three points located in the eastern, central, and western areas of Chaohu Lake, and then investigated sediment resuspension under hydraulic disturbances in the laboratory. The results showed that when the hydraulic disturbance is weak and sediment surface shear stress is small (<0.02 N/m²‌), sediment surface layer moves alone. When the hydraulic disturbance is moderate and sediment surface shear stress is within a threshold (3.7 N/m²‌), only a small proportion of the surface sediments begins to move. However, when the hydraulic disturbance is further strengthened and sediment surface shear stress is larger than the threshold value, surface sediments move smoothly. By the experimental results, we found that the plankton layer is about 1 mm (1.56% of the maximum content of suspended matter (SSCmax )), which is the major contribution of individual sediment initiation. The new sediment layer is about 19–22 mm (20.9% of the SSCmax ), which considerably affects sediment resuspension in shallow lakes. The consolidated layer is about 22 mm below the bed surface, which requires high shear stress and is hard to be transferred to the water column. The quantified experimental observation results are further verified with the theoretical results.